Surface roughness dependence of noncollinear phase matching - Martínez Matos, Oscar (2002)
Spontaneous noncollinear second harmonic generation in potassium dihydrogen phosphate (KDP) crystals was studied theoretically and experimentally as a function of the scattering centres on the surface of the crystal. A model that explains the main features of the second harmonic generated beam was developed in terms of the surface roughness defined by the size of the dispersing grains. It predicts, for the first time, the intensity distribution of the hollow cones obtained in noncollinear phase matching.